Theories of financial crises: An overview - Daniel Detzer; Hansjörg Herr (Hochschule für Wirtschaft und Recht Berlin, Institute for International Political Economy (IPE), 2014)
This paper analyses financial crises from a theoretical point of view. For this it reviews what different schools of economic thought have to say about financial crises. It examines first the approaches that regard financial crises as a disturbing factor of a generally stable real economy (Wicksell, Hayek, Schumpeter, Fisher, and the early Keynes). Thereafter, approaches, where the dichotomy between the monetary and the real sphere is lifted, are reviewed. Here in particular the later works of Keynes and the contributions of Minsky are of importance. Lastly, it is looked at the behavioural finance approaches. After having reviewed the different approaches, it is examined where those approaches have similarities and where they can be combined fruitfully. Based on this, we develop an own theoretical framework methodologically based on a Wicksellian cumulative process, however, overcoming the neoclassical dichotomy. The paper ends with some policy recommendations based on the developed theoretical framework.
Keywords: E03; E12; E13; G01; 330; financial crisis; crisis theory; behavioral finance; Hayek; Keynes; Minsky; Schumpeter; Wicksell